The peculiarities of the resistance to stress among coaches - Laskiene, S. (8th International Sports Science Conference, Vilnius, 25-26 February 2005, 2005)
By comparing the ways stress is perceived, experienced, and resisted by currently practising coaches and future coaches (the students learning to be coaches at the Lithuanian Academy of Physical Education), also by comparing their knowledge about stress, this research aims at determining the peculiarities of the resistance to stress among coaches.